Growth in chikungunya virus-related research in ASEAN and South Asian countries from 1967 to 2022 following disease emergence: a bibliometric and graphical analysis - Fajar Sofyantoro; Andri Frediansyah; Dwi Sendi Priyono; Wahyu Aristyaning Putri; Nur Indah Septriani; Nastiti Wijayanti; Winda Adipuri Ramadaningrum; Safaa A. Turkistani; Mohammed Garout; Mohammed Aljeldah; Basim R. Al Shammari; Ameen S. S. Alwashmi; et al. (Globalization and Health, 2023)
Abstract Background ASEAN (Association of Southeast Asian Nations) is composed of ten Southeast Asian countries bound by socio-cultural ties that promote regional peace and stability. South Asia, located in the southern subregion of Asia, includes nine countries sharing similarities in geographical and ethno-cultural factors. Chikungunya is one of the most significant problems in Southeast and South Asian countries. Much of the current chikungunya epidemic in Southeast Asia is caused by the emergence of a virus strain that originated in Africa and spread to Southeast Asia. Meanwhile, in South Asia, three confirmed lineages are in circulation. Given the positive correlation between research activity and the improvement of the clinical framework of biomedical research, this article aimed to examine the growth of chikungunya virus-related research in ASEAN and South Asian countries. Methods The Scopus database was used for this bibliometric analysis. The retrieved publications were subjected to a number of analyses, including those for the most prolific countries, journals, authors, institutions, and articles. Co-occurrence mapping of terms and keywords was used to determine the current state, emerging topics, and future prospects of chikungunya virus-related research. Bibliometrix and VOSviewer were used to analyze the data and visualize the collaboration network mapping. Results The Scopus search engine identified 1280 chikungunya-related documents published by ASEAN and South Asian countries between 1967 and 2022. According to our findings, India was the most productive country in South Asia, and Thailand was the most productive country in Southeast Asia. In the early stages of the study, researchers investigated the vectors and outbreaks of the chikungunya virus. In recent years, the development of antivirus agents has emerged as a prominent topic. Conclusions Our study is the first to present the growth of chikungunya virus-related research in ASEAN and South Asian countries from 1967 to 2022. In this study, the evaluation of the comprehensive profile of research on chikungunya can serve as a guide for future studies. In addition, a bibliometric analysis may serve as a resource for healthcare policymakers.